Tegument-Specific, Virus-Reactive CD4 T Cells Localize to the Cornea in Herpes Simplex Virus Interstitial Keratitis in Humans - Koelle, David M. (American Society for Microbiology, 2000)
Herpes stromal keratitis (HSK) is a prevalent and frequently vision-threatening disease associated with herpes simplex virus type 1 (HSV-1) infection. In mice, HSK progression occurs after viral clearance and requires T cells and neutrophils. One model implicates Th1-like CD4 T cells with cross-reactivity between the HSV-1 protein UL6 and a corneal autoantigen. HSK can be prevented by establishing specific immunological tolerance. However, HSK can also occur in T-cell receptor-transgenic X SCID mice lacking HSV-specific T cells. To study the pathogenesis of HSK in the natural host species, we measured local HSV-specific T-cell responses in HSK corneas removed at transplant surgery (n = 5) or control corneas (n = 2). HSV-1 DNA was detected by PCR in two specimens. HSV-specific CD4 T cells were enriched in three of the five HSK specimens and were not detectable in the control specimens. Reactivity with peptide epitopes within the tegument proteins UL21 and UL49 was documented. Responses to HSV-1 UL6 were not detected. Diverse HLA DR and DP alleles restricted these local responses. Most clones secreted gamma interferon, but not interleukin-5, in response to antigen. HSV-specific CD8 cells were also recovered. Some clones had cytotoxic-T-lymphocyte activity. The diverse specificities and HLA-restricting alleles of local virus-specific T cells in HSK are consistent with their contribution to HSK by a proinflammatory effect.